Functional connectivity of hippocampal and prefrontal networks during episodic and spatial memory based on real‐world environments. Issue 1 (10th September 2014) - Robin, Jessica; Hirshhorn, Marnie; Rosenbaum, R. Shayna; Winocur, Gordon; Moscovitch, Morris; Grady, Cheryl L.
ABSTRACT Several recent studies have compared episodic and spatial memory in neuroimaging paradigms in order to understand better the contribution of the hippocampus to each of these tasks. In the present study, we build on previous findings showing common neural activation in default network areas during episodic and spatial memory tasks based on familiar, real‐world environments (Hirshhorn et al. (2012) Neuropsychologia 50:3094–3106). Following previous demonstrations of the presence of functionally connected sub‐networks within the default network, we performed seed‐based functional connectivity analyses to determine how, depending on the task, the hippocampus and prefrontal cortex differentially couple with one another and with distinct whole‐brain networks. We found evidence for a medial prefrontal‐parietal network and a medial temporal lobe network, which were functionally connected to the prefrontal and hippocampal seeds, respectively, regardless of the nature of the memory task. However, these two networks were functionally connected with one another during the episodic memory task, but not during spatial memory tasks. Replicating previous reports of fractionation of the default network into stable sub‐networks, this study also shows how these sub‐networks may flexibly couple and uncouple with one another based on task demands. These findings support the hypothesis that episodic memory and spatial memory share a common medial temporal lobe‐based neural substrate, with episodic memory recruiting additional prefrontal sub‐networks. © 2014 Wiley Periodicals, Inc.